High-density, high-frequency and large-scale electrohydrodynamic drop-on-demand jetting via a protruding polymer-based printhead design - Yongqing Duan; Weili Yang; Qiming Wang; Zhaoyang Sun; Haoyu Guo; Zhouping Yin (Microsystems & Nanoengineering)
Abstract Electrohydrodynamic (EHD) printing has critical merits in micro/nanoscale additive manufacturing because of its ultrahigh resolution and wide ink compatibility, making it an advantageous choice for electronics manufacturing, high-resolution prototyping, and biological component fabrication. However, EHD printing is currently limited by its rather low throughput due to the lack of high-frequency and high-density multi-nozzle printheads. This paper presents a novel EHD printhead with a protruding polymer-based nozzle design. An insulated, hydrophobic, and protruding polymer nozzle array with an appropriate geometric structure can effectively address key problems in multi-nozzle jetting, such as electrical crosstalk, electrical discharge, liquid flooding, and nonuniform jetting. By investigating the influence of the electrical and geometric characteristics of the nozzle arrays on the electrical crosstalk behavior and fabricating the optimized nozzle array via MEMS technology, we achieve an EHD printhead with a large scale (256), high density (127 dpi), and high jetting frequency (23 kHz), and addressable jetting can be realized by adding independently controllable extractors underneath the nozzle array. Many functional materials, such as quantum dots, perovskite, and nanosilver inks, can be ejected into high-resolution patterns through the optimized nozzle array, demonstrating the great prospects of our designed printhead in electronics manufacturing. This MEMS-compatible printhead design lays the foundation for high-throughput fabrication of micro/nanostructures and promotes practical applications of EHD printing in functional electronics and biomedical/energy devices.